Język obcy w różnych modelach kształcenia uczniów g/Głuchych na przykładzie wybranych szkół specjalnych we Francji i w Polsce - Karpińska-Szaj, Katarzyna; Lewandowska, Agata (Neofilolog, 2025)
Deaf learners are a very heterogeneous group of language users. In many cases, they are plurilinguals with experiences related to the use of sign language, to hearing and speech rehabilitation, as well as verbal and sign communication in the immediate environment and at school. The model of language education applied in special institutions also has a significant impact on the cognitive development and communicative abilities of d/Deaf children. In this article, based on the results of a pilot study conducted among teachers of English as a foreign language, we analyse the impact of foreign language learning on the cognitive development and plurilingual competence of pupils in three special schools in France and Poland, representing different models of language instruction (including systemic bilingual education). In the analysed cases, learning a foreign language contributes to the development of pupils’ plurilingual competences, although this happens in different ways and to different extents.